2018
DOI: 10.1002/ett.3291
|View full text |Cite
|
Sign up to set email alerts
|

Optimal channel selection for simultaneous RF energy harvesting and data transmission in cognitive radio networks

Abstract: In this paper, a radio frequency–powered cognitive radio network is considered, in which the secondary users are powered by a radio frequency energy harvester (rectenna). Unlike most existing works, we consider a realistic rectenna characteristic function and derive the actual amount of harvested energy and thus obtain the resulting actual energy level of the secondary users. We consider a system architecture at which simultaneous energy harvesting and data transmission for each secondary user is possible. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Eh,kmt1 is the amount of the harvested energy by the k ‐th user of the m ‐th RRH during slot t −1 which is obtained as follows: Eh,kmtprefix−1=truef=1Mfalse(1prefix−αffalse)TtrueP^h,kmf,tprefix−1φkmf, where φkmf is an assignment index, φkmf is set to ‘1’ if the k ‐th user of the m ‐th RRH selects the f ‐th channel for energy harvesting. Also P^kmf,t1 is the amount of harvesting power by the k ‐th user of the m ‐th RRH during slot t −1 from channel f , which is obtained as below: trueP^h,kmf,tprefix−1=14RL{}false(2pkFnfalse|hkmffalse|2Rafalse)1false/2prefix−iVT2normalln()2πfalse(2pkFnfalse|hkmffalse|2Rafalse)…”
Section: Problem Formulation For a Pdma‐based Systemmentioning
confidence: 99%
“…Eh,kmt1 is the amount of the harvested energy by the k ‐th user of the m ‐th RRH during slot t −1 which is obtained as follows: Eh,kmtprefix−1=truef=1Mfalse(1prefix−αffalse)TtrueP^h,kmf,tprefix−1φkmf, where φkmf is an assignment index, φkmf is set to ‘1’ if the k ‐th user of the m ‐th RRH selects the f ‐th channel for energy harvesting. Also P^kmf,t1 is the amount of harvesting power by the k ‐th user of the m ‐th RRH during slot t −1 from channel f , which is obtained as below: trueP^h,kmf,tprefix−1=14RL{}false(2pkFnfalse|hkmffalse|2Rafalse)1false/2prefix−iVT2normalln()2πfalse(2pkFnfalse|hkmffalse|2Rafalse)…”
Section: Problem Formulation For a Pdma‐based Systemmentioning
confidence: 99%
“…This section surveys the existing techniques and algorithms related to Hooshiary et al suggested an optimal channel selection mechanism for managing the network traffic in CRN. The main intention of this paper was to select the best possible channels for allocation.…”
Section: Related Workmentioning
confidence: 99%
“…The multichannel selection was modeled as a convex optimization problem in [6], which maximized average throughput by controlling the channel selection probability. In [7], considering a realistic rectenna characteristic function, channels for energy harvesting and data transmission were selected simultaneously to improve system throughput. Multiple users were allowed to transmit on the same channel at the same time in [8] which judged the success of a transmission by the number of users access the same channel.…”
Section: Introductionmentioning
confidence: 99%